On Coordination of Secondary Cu(II) Dithizonate Complex - Hassanein, M.; Fouda, M.F.R.; Amin, R.S. (Asian Journal of Chemistry, 2010)
Secondary Cu(II) dithizonate complex was synthesised as solid from corresponding benzene-aqueous phase. IR,LF (ligand field), ESR and mass spectra together with thermal and elemental analysis of the complex were carried out. Generally, the spectral results suggested an approximately square planar coordination of copper ions, possibly with supplementary axial ligands. Moreover, the calculated value of G, 3.8, indicated the presence of some exchange coupling. However, the molecular structure of the complex is discussed in view of IR results as well as the computed spectroscopic g and Δ values.